PS01.127: SURGICAL RECONSTRUCTION OF ESOPHAGO-INTESTINAL CONTINUITY IN PATIENTS WITH SURGICAL CONDUIT FAILURE AFTER ESOPHAGEAL RESECTION AND RECONSTRUCTION. (14th September 2018) - Alghamdi, Zeead; Dong Lee, Geun; Sik Gong, Chung; Seob Lee, In; Su Kim, Beom; Wook Kim, Chan; Key Kim, Eun; Hee Kim, Yong
Abstract: Background: Surgical restoration of gastrointestinal tract integrity for failed esophageal conduit is technically challenging with significant morbidity and mortality. The purpose of this study was to evaluate the feasibility and safety of restored esophago-intestinal integrity for the failed reconstructed esophagus. Methods: From January 1990 to July 2017, a total of 1923 patients underwent esophageal cancer surgery. 29 patients (1.5%) presented with a clinical picture of failed conduits secondary to frank conduit necrosis, tracheoesophageal fistula, conduit stricture, and conduit cancer. We retrospectively analyzed 22 patients who planned to go for surgical reconstruction for a failed esophageal conduit. Results: The median age was 62.5 (14–72) years old, and all of the patients were males. The underlying pathology was esophageal squamous cell carcinoma for all patients. The interval between the first esophagectomy and the surgery for failed conduits was 14 days for conduit necrosis (n = 9), 43 days for TEF (n = 7), 1256 days for conduit stricture and 1520.5 days for conduit cancer(n = 4). Of the 22 patients, 18 patients (81.8%) underwent a successful surgical restoration of the esophago-intestinal integrity. Three of the remaining 4 patients who planned for reconstructive surgery died of pneumonia-related complications within 30 days and one patient elects to have a cervical esophagostomy.Among reconstructed patients, 14 patients had failed gastric conduit and 4 had failed colon conduit. For the gastric group, restoration of the gastrointestinal continuity achieved using esophagocolostomy in 12 patients, free jejunal flap in 1 patient and colon with a free jejunal flap in 1 patient. While in the colon group, restoration was accessible using free jejunal flaps in 2 patients, ileocolon in 1 patient and gastric conduit in 1 patient. During post-operative follow-up, 7 patients died with pneumonia or mediastinitis related complications, 3 died of cancer progression, and 1 unknown origin. The median survival time after conduit reconstruction was 36 months. Conclusion: Once a failed esophageal conduit is diagnosed, the decision of surgical reconstruction of gastrointestinal continuity can be feasible with a relatively good outcome if efficiently treated. In our study, reconstruction was possible in 81.8% of patients with a median survival time of 36 months after esophago-intestinal integrity restoration. Disclosure: All authors have declared no conflicts of interest.